Amelioratory Effect of Resistant Starch on Non-alcoholic Fatty Liver Disease via the Gut-Liver Axis - Zhu, Weifeng; Zhou, Ying; Tsao, Rong; Dong, Huanhuan; Zhang, Hua (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a hepatic manifestation of metabolic syndrome with a global prevalence. Impaired gut barrier function caused by an unhealthy diet plays a key role in disrupting the immune-metabolic homeostasis of the gut-liver axis (GLA), leading to NAFLD. Therefore, dietary interventions have been studied as feasible alternative therapeutic approaches to ameliorate NAFLD. Resistant starches (RSs) are prebiotics that reduce systemic inflammation in patients with metabolic syndrome. The present review aimed to elucidate the mechanisms of the GLA in alleviating NAFLD and provide insights into how dietary RSs counteract diet-induced inflammation in the GLA. Emerging evidence suggests that RS intake alters gut microbiota structure, enhances mucosal immune tolerance, and promotes the production of microbial metabolites such as short-chain fatty acids (SCFAs) and secondary bile acids. These metabolites directly stimulate the growth of intestinal epithelial cells and elicit GPR41/GPR43, FXR, and TGR5 signaling cascades to sustain immune-metabolic homeostasis in the GLA. The literature also revealed the dietary-immune-metabolic interplay by which RSs exert their regulatory effect on the immune-metabolic crosstalk of the GLA and the related molecular basis, suggesting that dietary intervention with RSs may be a promising alternative therapeutic strategy against diet-induced dysfunction of the GLA and, ultimately, the risk of developing NAFLD.